302 IS 18F-FDG PET/CT PARAMETERS USEFUL IN PREDICTING PATHOLOGICAL RESPONSE TO NEOADJUVANT CHEMORADIOTHERAPY FOR ESOPHAGEAL CARCINOMA?. (14th September 2020) - Tustumi, F; Takeda, F; Duarte, P; Albenda, D; Sallum, R; Ribeiro Junior, U; Buchpiguel, C; Cecconello, I
Abstract:  : The 18F-fluorodeoxyglucose positron emission tomography (FDG-PET/CT) provides an ability to functionally evaluate metabolic activity improving patient selection for surgical treatment. The value of SUVmax, MTV and TLG from FDG PET/CT of primary tumor and lymph nodes in the setting of neoadjuvant chemoradiotherapy for esophageal cancer in predicting pathological response to neoadjuvant therapy is the aim of this study. Methods: A retrospective cohort study was performed, assessing the correlation of SUVmax and volumetric parameters (MTV and TLG) of 18F-FDG PET/CT prior and post to neoadjuvant therapy for esophageal carcinoma with the pathological response as outcomes. Results: One hundred and seventeen patients were included. The higher AUC values in predicting pathological complete response were obtained for the primary tumor, on post neoadjuvant therapy. These variables showed high sensibility, but low specificity (SUVmax: AUC: 0.71, 95% CI: 0.55–0.87; MTV: AUC: 0.7, 95% CI: 0.54–0.86; TLG: AUC 0.71, 95% CI: 0.55–0.87). Conclusion: PET-Scan functionally evaluates metabolic activity, and the absolute values and changes of SUVmax and volumetric variables provide important information for pathological tumor response to neoadjuvant chemoradiotherapy.